Salivary microRNA profiling dysregulation in autism spectrum disorder: A pilot study - Kalemaj, Zamira; Marino, Maria Michela; Santini, Annamaria Chiara; Tomaselli, Giovanni; Auti, Amogh; Cagetti, Maria Grazia; Borsello, Tiziana; Costantino, Antonella; Inchingolo, Francesco; Boccellino, Mariarosaria; Di Domenico, Marina; Tartaglia, Gianluca Martino (Frontiers in Neuroscience, 2022)
Introduction: Autism spectrum disorders (ASD) are the most prevalent neurobiological disorders in children. The aetiology comprises genetic, epigenetic, and environmental factors such as dysfunction of the immune system. Epigenetic mechanisms are mainly represented by DNA methylation, histone modifications, and microRNAs (miRNA). The major explored epigenetic mechanism is mediated by miRNAs which target genes known to be involved in ASD pathogenesis. Salivary poly-omic RNA measurements have been associated with ASD and are helpful to differentiate ASD endophenotypes. This study aims to comprehensively examine miRNA expression in children with ASD and to reveal potential biomarkers and possible disease mechanisms so that they can be used to improve faction between individuals by promoting more personalized therapeutic approaches. Methods: Saliva samples were collected from 10 subjects: 5 samples of children with ASD and 5 from healthy controls. miRNAs were analyzed using an Illumina Next-Generation-Sequencing (NGS) system. Results: Preliminary data highlighted the presence of 365 differentially expressed miRNAs. Pathway analysis, molecular function, biological processes, and target genes of 41 dysregulated miRNAs were assessed, of which 20 were upregulated, and 21 were downregulated in children with ASD compared to healthy controls. Conclusions: The results of this study represent preliminary but promising data, as the identified miRNA pathways could represent useful biomarkers for the early non-invasive diagnosis of ASD.